A green molecular imprinted solid‐phase extraction protocol for bisphenol A monitoring with HPLC‐UV to guarantee the quality and safety of walnuts under different storage conditions. Issue 8 (29th January 2021) - Kalogiouri, Natasa P.; Pritsa, Agathi; Kabir, Abuzar; Furton, Kenneth G.; Samanidou, Victoria F.
Abstract: Monitoring the residual toxicant concentrations in foods is the key step for minimizing potential hazards. The huge interest about food contamination and exposure to endocrine disruptors such as bisphenol A has emerged the development of sensitive analytical methodologies to guarantee the safety and quality of foods. In this work, a green molecularly imprinted solid‐phase extraction protocol coupled with high‐performance liquid chromatography with UV detection was optimized following the principles of green analytical chemistry. An imprinted sol–gel silica‐based hybrid inorganic–organic polymeric sorbent was used to monitor the leaching of bisphenol A from different packaging materials (glass vessels, cans, and polypropylene containers) in walnuts stored within a period of 6 months at 25 and 4°C. Extraction parameters including loading time (5–20 min), solvent type (acetonitrile, ethanol, methanol, acetone, acetonitrile:methanol, 50:50, v/v), and elution flow rate (0.2–1 mL/min) were optimized with one‐factor‐at‐a‐time method. The selected extraction optimum parameters incorporated elution with acetonitrile at 0.2 mL/min flow rate, for 10 min sample holding time. The imprinting factor was equal to 4.55 ± 0.26 ( n = 3). The optimized method presented high recovery (94.3 ± 4.2%, n = 3), good linearity (>0.999), intra‐assay repeatability (90.2–95.6%, n = 3), and interassay precision (86.7–93.1%, n = 3).